Hydrogen sensing characteristics of vertical type hydrogen sensors based on porous 3C-SiC with catalyst materials - Kim, K. -S.; Chung, G. -S.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2013)
The hydrogen-sensing characteristics of porous 3C-SiC (p-SiC) with different catalyst metals were investigated. The scanning electron microscopy results confirm that the 3C-SiC film has a porous structure with a pore size of 20-30 nm. Hydrogen sensing behavior of Pd/p-SiC was analyzed as a function of hydrogen concentration by current-voltage (I-V) and a dagger I-t methods under steady state and transient conditions. The Pd was used as a Schottky contact and detection material. The Pt and Au catalyst metals were deposited on Pd layer to increase the hydrogen sensing characteristics. The change in current was monitored in the range of 210-610 ppm hydrogen concentrations. The deposited Pt was more sensitive to hydrogen gas than the Pd and Au catalyst metals. It is evaluated that the hydrogen sensing properties of porous 3C-SiC Schottky-diode can be improved by Pt and Pd catalytic metals.
Keywords: Silicon-Carbide; Gas Sensors; Pd